Pengaruh Penggunaan Model Pembelajaran Scramble Terhadap Hasil Belajar Pada Siswa Kelas IV Sekolah Dasar - Winni Safira Yuniarti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Education is one of the most important things in a person's life. Education will determine and guide one's future and the direction of one's life. According to Law no. 20 of 2003 concerning the National Education System, Education is a conscious and planned effort to create a learning atmosphere and learning process so that students can actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed himself, society, nation and state. Education is a conscious and planned effort, this means that the educational process in schools that is carried out between educators and students is directed at achieving educational goals. Education is to create a learning atmosphere and learning process. This means that in education, the process and learning outcomes should be in balance to form fully developed students.